Design of Y-shaped tri-band rectangular slot DGS patch antenna at sub-6 GHz frequency range for 5G communication - Ajay Singh; Sunil Joshi (Journal of Engineering and Applied Science, 2024)
Abstract This paper presents the design and development of a rectangular slot DGS patch antenna fed by a microstrip line, designed to operate across three distinct frequency bands at 4.0 GHz, 4.9 GHz, and 5.5 GHz for 5G wireless communication applications. The antenna design outlined in this study is implemented on a Fr-4 substrate with dimensions measuring 50.5 × 41.12 × 1.5 mm3. The antenna gains at three frequency bands are 2.69 dBi, 7.27 dBi, and 11.37 dBi having impedance bandwidths of 9%, 8.9%, and 5.1%, respectively. The attained bandwidths are 356 MHz, 443 MHz, and 287 MHz for the respective frequency bands. The radiation efficiencies of the proposed antenna are 90%, 82%, and 79% of the three respective frequencies. Antenna 1 in this study exhibits single-band behavior, effectively covering the single frequency band which is 5.5 GHz (5.3578–5.9519 GHz) 5G unlicensed band 5-GHz WLAN IEEE 802.11a frequency. On the other hand, Antenna 2 demonstrates dual-band characteristics spanning the S-band 3.7 GHz (3.5619–3.8544 GHz) and C-band range 5.1 GHz (4.8496–5.2008 GHz) suitable for mid-band 5G applications. Antenna 3 proposed antenna exhibits a tri-band functionality within the C-band spectrum. The results highlight multiple-band operation, consistent high gain, high directivity, and favorable directional radiation patterns.